TRPV4 participates in pressure‐induced inhibition of renin secretion by juxtaglomerular cells. (2nd December 2016) - Seghers, François; Yerna, Xavier; Zanou, Nadège; Devuyst, Olivier; Vennekens, Rudi; Nilius, Bernd; Gailly, Philippe
Abstract : Key points: Increase in blood pressure in the renal afferent arteriole is known to induce an increase in cytosolic calcium concentration ([Ca 2+ ]i ) of juxtaglomerular (JG) cells and to result in a decreased secretion of renin. Mechanical stimulation of As4.1 JG cells induces an increase in [Ca 2+ ]i that is inhibited by HC067047 and RN1734, two inhibitors of TRPV4, or by siRNA‐mediated repression of TRPV4. Inhibition of TRPV4 impairs pressure‐induced decrease in renin secretion. Compared to wild‐type mice, Trpv4 −/− mice present increased resting plasma levels of renin and aldosterone and present a significantly altered pressure–renin relationship. We suggest that TRPV4 channel participates in mechanosensation at the juxtaglomerular apparatus. Abstract: The renin–angiotensin system is a crucial blood pressure regulation system. It consists of a hormonal cascade where the rate‐limiting enzyme is renin, which is secreted into the blood flow by renal juxtaglomerular (JG) cells in response to low pressure in the renal afferent arteriole. In contrast, an increase in blood pressure results in a decreased renin secretion. This is accompanied by a transitory increase in [Ca 2+ ]i of JG cells. The inverse relationship between [Ca 2+ ]i and renin secretion has been called the 'calcium paradox' of renin release. How increased pressure induces a [Ca 2+ ]i transient in JG cells, is however, unknown. We observed that [Ca 2+ ]i transients induced by mechanical stimuli in JG As4.1 cells were completely abolished by HC067047 and RN1734, two inhibitors of TRPV4. They were also reduced by half by siRNA‐mediated repression of TRPV4 but not after repression or inhibition of TRPV2 or Piezo1 ion channels. Interestingly, the stimulation of renin secretion by the adenylate cyclase activator forskolin was totally inhibited by cyclic stretching of the cells. This effect was mimicked by stimulation with GSK1016790A and 4αPDD, two activators of TRPV4 and inhibited in the presence of HC067047. Moreover, in isolated perfused kidneys from Trpv4 −/− mice, the pressure–renin relationship was significantly altered. In vivo, Trpv4 −/− mice presented increased plasma levels of renin and aldosterone compared to wild‐type mice. Altogether, our results suggest that TRPV4 is involved in the pressure‐induced entry of Ca 2+ in JG cells, which inhibits renin release and allows the negative feedback regulation on blood pressure. Key points: Increase in blood pressure in the renal afferent arteriole is known to induce an increase in cytosolic calcium concentration ([Ca 2+ ]i ) of juxtaglomerular (JG) cells and to result in a decreased secretion of renin. Mechanical stimulation of As4.1 JG cells induces an increase in [Ca 2+ ]i that is inhibited by HC067047 and RN1734, two inhibitors of TRPV4, or by siRNA‐mediated repression of TRPV4. Inhibition of TRPV4 impairs pressure‐induced decrease in renin secretion. Compared to wild‐type mice, Trpv4 −/− mice present increased resting plasma levels of renin and aldosterone and present a significantly altered pressure–renin relationship. We suggest that TRPV4 channel participates in mechanosensation at the juxtaglomerular apparatus.